Pengaruh Toksisitas Akut Ekstrak Etanol Rimpang Pacing (Costus speciosus) pada Embrio Zebrafish (Danio rerio) - Kharina Septi Lestari; Aulia Utami Widiati; Aulia Nurfazri Istiqomah (Indonesian Journal of Herbal Science and Innovation, 2025)
The Costus speciosus plant, commonly known as pacing, is widely used both as an ornamental plant and in traditional medicine. All parts of the plant, particularly the rhizomes, are known to possess various pharmacological activities, including anti-diabetic, anti-cancer, anti-bacterial, and anti-inflammatory properties. However, with the extensive use of the rhizomes in traditional medicine, it is essential to assess their safety. This study aims to determine the LC50 value of ethanol extract from Costus speciosus rhizomes (EERP) and evaluate its acute toxicity level. The Fish Embryo Acute Toxicity (FET) Test was used to assess toxicity, employing zebrafish (Danio rerio) embryos as the model organism. Zebrafish are chosen because their genetic makeup shares about 60-70% similarity with humans, making them a suitable model for mapping toxic effects. The study involved seven experimental groups: two control groups (negative and positive controls) and five groups treated with varying concentrations of EERP (62.5 ppm, 31.25 ppm, 15.63 ppm, 7.81 ppm, and 3.91 ppm). The results revealed an LC50 value of 11.707 ppm for EERP, indicating that the extract falls under the "slightly toxic" category. These findings provide valuable insights into the potential toxicity of Costus speciosus, which is crucial for determining safe dosage levels in its use as a traditional medicine. Further research is needed to explore the underlying toxic mechanisms of this extract.